Positive efficiency of optical wavelength conversion based-on degenerate fwm in injection-locked raman ring laser - Zamzuri, Abdul Kadir; Ismail, U. S.; Mahdi, Mohd Adzir (2007)
This paper purposes wavelength conversion (WC) that is based on degenerated Four-Wave Mixing (DFWM) assisted by Raman amplification occuring in highly nonlinear fiber (HNLF). The uniqueness of this design is it requires only single external lightsource functioning as a signal source. The pump source is internally created with the assistance of Raman amplification through ring resonator. Besides helping generate idlers, the pump also works as gain locking element to the incoming signal hence indirectly controls conversion parameters. The arrangement of indorporated components such as variable coupler, circulator and fiber grating also provide the design some flexibility in terms of lasing output power, propagation scheme and other parameters. A positive conversion-efficiency (CE) of 19.5 nm around the pump wavelength, the widest yet reported using the HNLF irrespective to the flattened value of CE, was obtaoned. This broad positive-CE reflecting a 1-Regenerator (I-R) feature is attributed to the high cavity gain achieved from this design.